Changing Inequality Structures in Europe: The Challenge to Social Science - Lee Rainwater (Luxembourg Income Study (LIS), 1990)
In order to understand inequality in rapidly changing Europe, innovations in data collection and research methods will be essential. Related issues are illustrated through discussion of several different aspects of inequality using the LIS database.
Keywords: 330; Lebensstandard; Einkommensverteilung; Europa